2012
DOI: 10.1094/mpmi-09-11-0240
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma harzianum Enhances Antioxidant Defense of Tomato Seedlings and Resistance to Water Deficit

Abstract: Some plant-symbiotic strains of the genus Trichoderma colonize roots and induce profound changes in plant gene expression that lead to enhanced growth, especially under biotic and abiotic stresses. In this study, we tested the hypothesis that one of the protective mechanisms enhanced by T. harzianum T22 colonization is the antioxidant defense mechanism. Having established that strain T22 modulates the expression of the genes encoding antioxidant enzymes, the status of antioxidant defense of tomato seedlings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
105
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(128 citation statements)
references
References 37 publications
17
105
2
4
Order By: Relevance
“…Drought tolerant rhizobacteria are capable of synthesizing ROS scavenging enzyme, especially under drought stress and increase photosynthetic efficiency and thus, helping the plants to cope with drought stress. Similar alterations in antioxidative capacity by stress-alleviating microorganisms have been reported earlier (Wang et al 2012;Mastouri et al 2012). ROS detoxification enzyme is an important microbial trait for screening drought stress alleviating potential microorganisms.…”
Section: Microbial Integrity For Plant Fitness Under Moisture Stressesupporting
confidence: 77%
See 1 more Smart Citation
“…Drought tolerant rhizobacteria are capable of synthesizing ROS scavenging enzyme, especially under drought stress and increase photosynthetic efficiency and thus, helping the plants to cope with drought stress. Similar alterations in antioxidative capacity by stress-alleviating microorganisms have been reported earlier (Wang et al 2012;Mastouri et al 2012). ROS detoxification enzyme is an important microbial trait for screening drought stress alleviating potential microorganisms.…”
Section: Microbial Integrity For Plant Fitness Under Moisture Stressesupporting
confidence: 77%
“…Superoxide (O 2 − ) and hydrogen peroxide (H 2 O 2 ) are other two species of antioxidants found in plant under drought stress. Rhizobacteria by virtue of elaborating superoxide dismutase (SOD) (EC 1.15.1.1) and catalase (CAT) (EC 1.11.1.6) scavenge those antioxidants and help the plant to survive in restricted moisture condition (Mastouri et al 2012).…”
Section: Microbial Integrity For Plant Fitness Under Moisture Stressementioning
confidence: 99%
“…However, the ability of these fungi to sense, invade, and destroy other fungi has been the major driving force behind their commercial success as biopesticides (more than 60% of all registered biopesticides are Trichoderma-based) (136). These fungi not only protect plants by killing other fungi and certain nematodes but induce resistance against plant pathogens, impart abiotic stress tolerance, improve plant growth and vigor, solubilize plant nutrients, and bioremediate heavy metals and environmental pollutants (53,78,81,126). In addition, this genus comprises fungi that produce secondary metabolites of clinical significance and enzymes with widespread industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…The biocontrol mechanisms are based on the production of antibiotics (2,3) and/or hydrolytic enzymes as well as competition for nutrients (4). In addition, Trichoderma strains are also able to stimulate defense responses in plants, inducing resistance to biotic and abiotic stresses, and to promote plant growth (5)(6)(7). Several studies have reported the responses of plants to the presence of a rootcolonizing Trichoderma biocontrol strain (8)(9)(10)(11)(12), and investigations describing the Trichoderma transcriptomic changes elicited by plants using macroarray (13,14) and microarray (15,16) analyses have been performed with biocontrol species.…”
mentioning
confidence: 99%